Delayed tooth replantation: MTA as root canal filling - Sônia Regina PANZARINI; Celso Koogi SONODA; Célia Tomiko Matida Hamata SAITO; Elizane Ferreira HAMANAKA; Wilson Roberto POI (Sociedade Brasileira de Pesquisa Odontológica, 2014)
MTA has been investigated as a root-end filling material. Its mechanism of action has some similarities to that of Ca(OH)2. The purpose of this study was to evaluate the repair process taking place in the delayed replantation of monkey teeth using calcium hydroxide and MTA as root canal filling materials. Five monkeys had their lateral incisors extracted and bench-dried for 60 minutes. After root canal preparation, the teeth were assigned to two groups according to root canal filling material: I, calcium hydroxide; and II, MTA. The same treatment sequence was followed for both groups: coronal seal, periodontal ligament removal, immersion of the tooth in 2% acidulated-phosphate sodium fluoride, irrigation of the socket with saline and replantation. Both groups exhibited replacement resorption, areas of ankylosis and absence of inflammatory root resorption. Statistically similar results (p > 0.05) were observed for both groups regarding replacement root resorption, but the groups differed significantly (p < 0.05) regarding the occurrence of ankylosis. MTA may be a viable clinical option for filling teeth submitted to delayed replantation, and is an acceptable option for treating replanted permanent teeth in order to prevent tooth resorption, particularly when dressing changes are not possible.